5 - Supporting University ICT Developments: The Makerere University Experience: DOI: 10.4314/ad.v30i1.22214 - Tusubira, Francis Frederick (Africa Development, 2005)
The integration of information and communication technology (ICT) services and systems into the functions of an enterprise will be easier when there is a clearly identified strategic need, with ICT responding to the vision and strategic priorities. The experience of Makerere University is used to highlight best practice approaches to addressing the key challenges of: lack of awareness; mindset and fear; the proc ess; and sustainability. It is argued that a good ICT policy and master plan devel oped with the full participation of the stakeholders is a key ingredient for success.